Inequality and the generational economy: Race-disaggregated National Transfer Accounts for South Africa, 2015 - Morné Oosthuizen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Differences in the economic lifecycle between countries at different levels of development suggest that there may be differences between sub-populations within countries, particularly where the sub-populations have different levels of income. Given stark inequalities by race in South Africa, this paper constructs a full set of race-disaggregated National Transfer Accounts for 2015 and finds substantial differences between them in patterns of producing, consuming, sharing, and saving across the lifecycle. Resources flow strongly downwards to younger cohorts for all groups, while older Africans make large transfers to household members when compared with their counterparts of other races. Differences in the financing of consumption at older ages between race groups suggest that South Africa's second demographic dividend may be overstated by reliance on national-level profiles. The results suggest that National Transfer Accounts-based estimates of the demographic dividends would benefit from accounting for differences between sub-populations.
Keywords: J10; E01; J11; J15; 330; demographic dividend; economic lifecycle; intergenerational transfers; National Transfer Accounts; race; South Africa